Effect of wear progression in an 'S'-type mixed ceramic tool on machining forces and surface roughness in the turning of hardened AISI 4140 steel. (6th May 2019) - Nicolodi, Jéferson Hilário W.; Consalter, Luiz Airton; Durán, Orlando; Souza, André J.
This study investigates the behaviours of machining forces and the roughness of a workpiece in the dry turning of AISI 4140 steel hardened at 55 HRC due to the wear evolution of a mixed ceramic tool with 'S'-type blade microgeometry. Six end-of-life tests were performed by combining three levels of cutting speed and two feed rate levels. A constant depth of cut was maintained. According to the results, the highest cutting speed and feed rates had a significant effect on the flank and crater wear of the tool and gradually changed the values of the forces and roughness. The feed rate was the parameter with the highest effect on the output parameters of the process. The crater wear evolution caused a reduction of the machining forces. Meanwhile, flank wear formation promoted an increase in the machining force components. From the point of view of the influence of tool wear processes, and, unlike what happens with flank wear, the crater formation affects favourably the surface roughness, as its evolution promoted the reduction of the Ra values in all cutting conditions.